Influence of the HLA characteristics of Italian patients on donor search outcome in unrelated hematopoietic stem cell transplantation. Issue 2 (18th April 2014) - Testi, M.; Andreani, M.; Locatelli, F.; Arcese, W.; Troiano, M.; Battarra, M.; Gaziev, J.; Lucarelli, G.
Abstract The information regarding the probability of finding a matched unrelated donor (MUD) within a relatively short time is crucial for the success of hematopoietic stem cell transplantation (HSCT), particularly in patients with malignancies. In this study, we retrospectively analyzed 315 Italian patients who started a search for a MUD, in order to assess the distribution of human leukocyte antigen (HLA) alleles and haplotypes in this population of patients and to evaluate the probability of finding a donor. Comparing two groups of patients based on whether or not a 10/10 HLA‐matched donor was available, we found that patients who had a fully‐matched MUD possessed at least one frequent haplotype more often than the others (45.6% vs 14.3%; P = 0.000003). In addition, analysis of data pertaining to the HLA class I alleles distribution showed that, in the first group of patients, less common alleles were under‐represented (20.2% vs 40.0%; P = 0.006). Therefore, the presence of less frequent alleles represents a negative factor for the search for a potential compatible donor being successful, whereas the presence of one frequent haplotype represents a positive predictive factor. Antigenic differences between patient and donor observed at C and DQB1 loci, were mostly represented by particular B/C or DRB1/DQB1 allelic associations. Thus, having a particular B or DRB1 allele, linked to multiple C or DQB1 alleles, respectively, might be considered to be associated with a lower probability of a successful search. Taken together, these data may help determine in advance the probability of finding a suitable unrelated donor for an Italian patient.